Atherosclerotic Risk Factor Prevalence in Adults With Congenital Heart Disease - Andreas S. Papazoglou, MD, MSc; Konstantinos G. Kyriakoulis, MD, PhD; Konstantinos Barmpagiannos, MD; Dimitrios V. Moysidis, MD, MSc; Anastasios Kartas, MD, PhD; Maria Chatzi, MD, MSc; Amalia Baroutidou, MD, MSc; Vasileios Kamperidis, MD, PhD; Antonios Ziakas, MD, PhD; Konstantinos Dimopoulos, MD, PhD; George Giannakoulas, MD, PhD (JACC: Advances, 2024)
Background: The risk of atherosclerotic cardiovascular disease (ASCVD) in adults with congenital heart disease (ACHD) is comparable to that of the general population and is driven by traditional ASCVD risk factors. Objectives: The aim of the study was to estimate the prevalence of traditional ASCVD risk factors (hypertension, dyslipidemia, diabetes mellitus [DM], obesity, smoking, and physical inactivity) in ACHD and compare it with the general population. Methods: A systematic literature search was conducted up to May 15, 2024, to identify studies (with or without control group) reporting the prevalence of ASCVD risk factors in ACHD. Meta-analyses were conducted to synthesize the prevalence of risk factors and compare it with that of the general population, where applicable. Results: We identified 62 studies (30 controlled) encompassing 110,469 ACHD (mean age 39 years; 52% males, 88% with simple/moderate congenital heart disease complexity). Of these, 54% (45%-63%) reported lack of regular exercise, 33% (26%-40%) had hypertension, 18% (14%-22%) were obese, 17% (11%-25%) had dyslipidemia, 12% (9%-14%) were current smokers, and 7% (5%-9%) had DM. The prevalence of ASCVD risk factors was similar in ACHD and controls, with the exception of DM (higher prevalence in ACHD) and smoking (lower prevalence in ACHD). Significant heterogeneity was observed among the included studies, partially explained by differences in age, congenital heart disease complexity, and the presence of cyanosis. Conclusions: Except for DM and smoking, the prevalence of traditional ASCVD risk factors is similar in ACHD compared to the general population. Further research is needed to determine whether interventions applied in the general population are also effective in ACHD.